2011
DOI: 10.1021/jp205532e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Block Copolymer Lithography Using Sequential Infiltration Synthesis

Abstract: INTRODUCTIONSelf-assembly of block copolymer (BCP) thin films has been explored extensively as a strategy to make periodic nanostructures. 1À4 Because these nanoscale features can be formed reproducibly and at low-cost, there is tremendous interest in transferring such patterns to functional materials. In particular, BCP films are promising for microelectronics and data storage applications where highly dense and periodic nanoscale patterns are needed over a large area. 5À8 BCP films can self-organize to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
190
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(192 citation statements)
references
References 29 publications
2
190
0
Order By: Relevance
“…Figure 9 b-d shows highfi delity silicon nanostructures perpendicular and parallel to the substrate plane following pattern transfer using an Al 2 O 3 hardmask via SIS. [ 113 ] Subsequently, Black and co-workers illustrated high-aspect ratio pattern transfer using the same SIS approach for PSb -PMMA (see Figure 9 e-g). [ 114 ] Systematic studies were carried out analysing the Al 2 O 3 infi ltration effect on domains which showed that image quality suffered with higher ALD cycles.…”
Section: Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 9 b-d shows highfi delity silicon nanostructures perpendicular and parallel to the substrate plane following pattern transfer using an Al 2 O 3 hardmask via SIS. [ 113 ] Subsequently, Black and co-workers illustrated high-aspect ratio pattern transfer using the same SIS approach for PSb -PMMA (see Figure 9 e-g). [ 114 ] Systematic studies were carried out analysing the Al 2 O 3 infi ltration effect on domains which showed that image quality suffered with higher ALD cycles.…”
Section: Reviewmentioning
confidence: 89%
“…Impressive reports by Checco et al [ 117,118 ] and Rahman et al [ 119,120 ] [ 113 ] Copyright 2011, American Chemical Society. e-g) Reproduced with permission.…”
Section: Reviewmentioning
confidence: 99%
“…[145][146][147][148][149][150][151] Driven by entropic and enthalpic interactions between both blocks micro-phase separation structures are formed which have characteristic repeat distances on the order of 10 nanometers. [152][153][154] The polymer-polymer interaction parameter between the blocks, the block ratio, the polydispersity, as well as the molecular weight of the block copolymer determine the morphology of the micro structures. [155,156] Thermodynamic equilibrium results in well-defined nanostructures, which can be spherical, cylindrical, gyroid and lamellar structures.…”
Section: Morphology Control Using Insulating Block Copolymersmentioning
confidence: 99%
“…Interestingly, they can also serve as intermediate patterns for the preparation of inorganic nanostructures, with a myriad of potential applications such as active devices [26] or hard mask for lithographic process [27]. The transformation of such organic films into silica templates can be performed using sequential infiltration synthesis (SIS) if one polymer could be selectively infiltrated with inorganic gas-phase precursors by diffusion [27][28][29]. This has been done with poly(styrene) (PS) and poly(methyl methacrylate) (PMMA) blends, where gaseous trimethylaluminum (TMA) and water selectively diffuse into PMMA.…”
Section: Introductionmentioning
confidence: 99%